Nickel‐free high‐nitrogen austenitic steel outperforms CoCrMo alloy regarding tribocorrosion in simulated inflammatory synovial fluids. Issue 6 (7th September 2021) - Radice, Simona; Neto, Mozart Q.; Fischer, Alfons; Wimmer, Markus A.
Abstract: CoCrMo alloys are well‐established biomaterials used for orthopedic joint replacement implants. However, such alloys have been associated with clinical problems related to wear and corrosion. A new generation of austenitic high‐nitrogen steels (AHNSs) has been developed for biomedical applications. Here, we have addressed influences of hyaluronic acid, combined with inflammatory (oxidizing) conditions, on tribocorrosion of the high‐nitrogen FeCrMnMoN0.9 steel (DIN/EN X13CrMnMoN18‐14‐3, 1.4452), and of the low carbon CoCrMo0.03 alloy (ISO 5832‐12). We aimed to elucidate critical and clinically relevant conditions affecting the implant's performance in certain orthopedic applications. Tribocorrosion tests were conducted in triplicate, with discs under reciprocating sliding wear against a ceramic ball. Different lubricants were prepared from standardized bovine serum solution (ISO 14242‐1), with variable additions of hyaluronic acid (HA) and hydrogen peroxide (H2 O2 ). Test conditions were: 37°C, 86, 400 cycles, 37 N load (20–40 MPa after run‐in phase). Volumetric wear was quantified; surfaces were evaluated by electrochemical parameters and microscopy/spectroscopy analyses (SEM/EDS). Factorial analysis of variance tests was conducted to examine the effects of HA, H2 O2, and test material on wear‐ and corrosion‐related dependent variables. Tribocorrosion performances of CoCrMo0.03 and FeCrMnMoN0.9 were comparable in fluids without H2 O2 . With higher H2 O2 concentrations, tribocorrosion increased for CoCrMo0.03, while this was not the case for FeCrMnMoN0.9 . HA significantly enhanced wear of CoCrMo0.03 in the absence of H2 O2, while it mitigated the tribocorrosive action of 3 mM H2 O2 ; HA had no impact on FeCrMnMoN0.9 . These results indicate a favorable performance of FeCrMnMoN0.9 compared to CoCrMo0.03, and encourage further research on AHNS for certain orthopedic applications. Abstract : Austenitic high nitrogen steels (AHNS) are candidate materials to replace CoCrMo‐alloys for orthopedic implant components, with matching the mechanical properties. This is the first study comparing tribocorrosion between AHNS and CoCrMo with clinically relevant test parameters and fluids.